Is there an association between adolescent’s personality traits and their liking behavior on social networking sites? - Þóra Kristín Ómarsdóttir 1995- (2019)
On social networking sites, such as Facebook and Instagram, there is a like button that allows users to express if they like a post by someone else and receive likes on their own posts. This is a type of a communication behavior that occurs in the daily lives of social networking site users. The aim of this study is to further examine liking behavior of adolescents. It is a replication of a previous study by Hong, Chen, & Li in 2017 with some additions and investigates if and how different personality traits are associated with frequency of giving likes and how important it is to receive them on Facebook and Instagram. A questionnaire was sent to 8th, 9th, and 10th grades in two secondary schools in Kópavogur, Iceland. The results of the study revealed association between perceived importance of receiving likes on Instagram and self-esteem and public self-consciousness. Public self-consciousness was also found associated with perceived importance of receiving likes on Facebook. No association was found between any of the examined personality traits and frequency of giving likes on Facebook and Instagram. Á samfélagsmiðlum er hnappur sem hægt er að ýta á til þess að „líka við“ færslu annarra og sömuleiðis fá það frá öðrum á sínar eigin færslur. Þetta er tegund af samskiptahegðun sem á sér stað í daglegu lífi notenda samfélagsmiðla. Markmið þessarar rannsóknar er að rannsaka þessa samskiptahegðun hjá unglingum. Þessi rannsókn er endurgerð rannsókn sem Hong, Chen og Li gerðu árið 2017 með nokkrum viðbætum. Markmið rannsóknarinnar er að kanna hvort og hvernig persónuleikaeinkenni hafa áhrif á tíðni þess að „líka við“ færslur annarra og hversu mikilvægt það er að fá aðra til þess að „líka við“ eigin færslur á Facebook og Instagram. Spurningalisti var sendur til 8., 9., og 10. bekkjar í tveimur skólum í Kópavogi. Niðurstöðurnar sýndu að það væri samband á milli bæði sjálfsálits og opinberar sjálfsvitundar við hversu mikilvægt notandi upplifir að það sé að aðrir ,,líki við“ færslur á Instagram. Einnig fundust ...